2022
DOI: 10.33369/pendipa.6.2.565-572
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Hasil Belajar Peserta Didik melalui Implementasi Pembelajaran Berbasis Assessment for Learning pada Materi Kesetimbangan Kimia

Abstract: The aim of this research was to describe the implementation of assessment for learning, student activities during learning activities, improving learning outcomes of chemical equilibrium material, and student responses to assessment for learning. The subjects of this study were students of class XI MIPA 4 at SMAN 3 Surabaya. This study uses a pre-experimental research design using One Group Pretest-Posttest Design. The results of this study show that (1) the quality of the implementation of assessment for lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It is intended that this will lead to student engagement (student center), with the instructor serving only as a facilitator. According to research conducted by Dini & Muchlis, (2022) student learning outcomes in chemical equilibrium material can be improved by assessment for learning by 87.88% in the high N-gain category and by 12,12% in the medium N-gain category. Safithri & Muchlis (2022), claimed that student learning outcomes in reaction rate material can be enhanced by assessment for learning by 97.22% in the high Ngain category and by 2.78% in the medium N-gain category.…”
Section: Introductionmentioning
confidence: 99%
“…It is intended that this will lead to student engagement (student center), with the instructor serving only as a facilitator. According to research conducted by Dini & Muchlis, (2022) student learning outcomes in chemical equilibrium material can be improved by assessment for learning by 87.88% in the high N-gain category and by 12,12% in the medium N-gain category. Safithri & Muchlis (2022), claimed that student learning outcomes in reaction rate material can be enhanced by assessment for learning by 97.22% in the high Ngain category and by 2.78% in the medium N-gain category.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that learning based on the assessment for learning approach can improve learning effectiveness. For example, [15] showed that applying afl assessment-based learning can improve students' learning outcomes on chemical equilibrium materials. Another study by [16] also found that assessment for learning-based learning effectively enhances students' learning outcomes, especially for reaction rate materials.…”
Section: Introductionmentioning
confidence: 99%